Research and Development in Intelligent Systems XXXI Incorporating Applications and Innovations in Intelligent Systems XXII - Bramer, Max.; Petridis, Miltos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The papers in this volume are the refereed papers presented at AI-2014, the Thirty-fourth SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence, held in Cambridge in December 2014 in both the technical and the application streams. They present new and innovative developments and applications, divided into technical stream sections on Knowledge Discovery and Data Mining, Machine Learning, and Agents, Ontologies and Genetic Programming, followed by application stream sections on Evolutionary Algorithms/Dynamic Modelling, Planning and Optimisation, and Machine Learning and Data Mining. The volume also includes the text of short papers presented as posters at the conference. This is the thirty-first volume in the Research and Development in Intelligent Systems series, which also incorporates the twenty-second volume in the Applications and Innovations in Intelligent Systems series. These series are essential reading for those who wish to keep up to date with developments in this important field.
Research and Development in Intelligent Systems XXXI Best Technical Paper -- On Ontological Expressivity and Modelling Argumentation Schemes using COGUI -- Knowledge Discovery and Data Mining -- Computationally Efficient Rule-Based Classification for Continuous Streaming Data -- Improved Stability of Feature Selection by Combining Instance and Feature Weighting -- Towards a parallel Computationally Efficient Approach to Scaling up Data Stream Classification -- Machine Learning.-Following the Trail of Source Languages in Literary Translations -- Reluctant Reinforcement Learning -- Preference and Sentiment Guided Social Recommendations with Temporal Dynamics -- Agents, Ontologies and Genetic Programming.-Query Failure Explanation in Inconsistent Knowledge Bases: A Dialogical Approach -- Benchmarking Grammar-Based Genetic Programming Algorithms -- The Effects of Bounding Rationality on the Performance and Learning of CHREST Agents in Tileworld -- Short Papers -- An Autopoietic Repertoire -- De-Risking Fleet Replacement Decisions -- Reliability and Effectiveness of Cross-Validation in Feature Selection -- Self Reinforced Meta Learning for Belief Generation -- Applications and Innovations in Intelligent Systems XXII Best Application Paper -- Combining Semantic Web Technologies with Evolving Fuzzy Classifier eClass for EHR-based Phenotyping: A Feasibility Study -- Evolutionary Algorithms/Dynamic Modelling -- Rail-Freight Crew Scheduling with a Genetic Algorithm -- CR-Modified SOM to the Problem of Handwritten Digits Recognition -- Dynamic Place Profiles from Geo-Folksonomies on the GeoSocial Web -- Planning and Optimisation -- Hierarchical Type-2 Fuzzy Logic Based Real Time Dynamic Operational Planning System -- A Hybrid Algorithm for Solving Gate Assignment Problem with Robustness and Tow Considerations -- An Iterative Heuristics Algorithm for Solving the Integrated Aircraft and Passenger Recovery Problem -- Machine Learning and Data Mining.-A Framework for Brand Reputation Mining and Visualisation -- A Review of Voice Activity Detection Techniques for On - device Isolated Digit Recognition on Mobile Devices -- Short Papers -- Ontology-Based Information Extraction and Reservoir Computing for Topic Detection from Blogosphere's content: A Case Study about BBC Backstage -- A Study on Road Junction Control Method Selection Using an Artificial Intelligent Multi-Criteria Decision Making Framework.
Keywords: Artificial intelligence; Data mining; Artificial Intelligence; Data Mining and Knowledge Discovery